Coefficient Problems on Bi-Univalent Functions With \((p,q)\)-Gegenbauer Polynomials - Raju, R. Govinda; Salestina, M. Ruby; Gatti, N. B. (Communications in Mathematics and Applications, 2024)
In this paper, our main aim is to study a new subclass of bi-univalent functions and to obtain initial coefficient bounds of starlike and convex bi-univalent functions involving \((p,q)\)-Gegenbauer polynomials. Also, we aim at obtaining sharp bound for Fekete-Szegö functional.